Promoting Economic Literacy: Panel Discussion - Lucas, Robert E; Krueger, Alan B; Blank, Rebecca M (American Economic Review, 2002)
Robert E. Lucas, Jr.:' January 2002 issue of the Atlantic contains an article by Benjamin Schwarz and Christopher Layne called A New Grand Strategy. article deplores the role of the United States in the Middle East, which the authors interpret as derived from a perceived need to ensure the availability of from that region. As the authors observe, America derives most of its from Alaska, Canada, the continental United States, Mexico, and Venezuela. About 25 percent of U.S. petroleum imports come from the Persian Gulf. If the United States adopted a national energy strategy it could free itself from dependence on Persian Gulf oil (p. 37). They go on to advocate doing this, and leaving Middle East politics to other, still dependent powers. They explain: The role the United States has assigned itself in the Persian Gulf has made it-not Japan, not the states of Western Europe, not China-vulnerable to a backlash (p. 38). Schwarz and Layne article is a good example of what W. Lee Hansen et al. (2002 [preceding paper, this issue]) call illiteracy. Its entire argument is based on the market for oil, but the authors do not have even an Economics 101 understanding of what a market is. They construct a vision of a new U.S. foreign policy based on a wholly arbitrary matching up of particular buyers of a homogeneous good with particular sellers of the good. We will exercise hegemony in Mexico and Venezuela, they say, and let the Japanese take care of the Middle East. example illustrates three points emphasized in Use or Lose It: Teaching Literacy in the Economics Principles Course (this issue, preceding paper). First, economic illiteracy often is an affliction of the well-educated: Schwarz and Layne are articulate experts in foreign affairs. Second, economic illiteracy can be dangerous: there is more at stake than bad answers to our exam questions. Third, the ignorance involved is not ignorance of the research tools of technical economics. should not be necessary to be handy with fixed-point theorems in order to avoid mistakes like the one Schwarz and Layne make. Use or Lose It has two main theses. first is that we can and should promote economic literacy by redesigning the first collegelevel economics course (one semester) to teach principles, not methods. second is that we can use a list of 20 Content Standards provided by the National Council on Economic Education to define what it means to teach principles. I have misgivings about both these theses, to which I turn in a moment. I must say at the outset, though, that my criticism will be almost entirely nonconstructive: I agree that introductory economics needs to be reinvented, but I do not claim to know how to do it. In criticizing introductory economics courses and textbooks, the authors lament the increasingly technical nature of the course and cite others who share this view. Nostalgia is expressed (in a quote from McConnell, not a direct statement by these authors) for a 1946 text of Frank Taussig's that predates even my ancient training by 15 years! would be hard to think of a surer way to discourage the most able students from pursuing a career in economics than to offer them a 50-year-old textbook on the grounds that P. J. O'Rourke did not like graphs. Imagine proposing such a thing to an association of physicists or chemists or, for that matter, musicologists! Knowledge is cumulative-a fact that should make us happy, not sad. One of our jobs as teachers is to help our most eager and creative students get to the knowledge frontier as fast as they want to go. In the natural sciences and the arts, introductory courses are professionally oriented basic-training courses on which one can build a creative career. Economics students deserve as much. problem with leaving the matter at this is that introductory science courses tend to be useless for nonmajors. Indeed, levels of physics literacy, chemistry literacy, and musical literacy among well-educated people are in no better shape than economics literacy. This is the classic case against letting each student design his 'Department of Economics, University of Chicago, 1126 East 59th St., Chicago, IL 60637.